(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Objective: To collect and document information of anti-diabetic plants traditionally used in the treatment of Diabetes Mellitus in Sankhuwasabha district of Nepal as ethno medicines are important part of treatment in this area and such information are considered as valuable sources of information to find new potential drugs. Methods: Direct observation and interview method with 46 traditional healers along with gathering herbarium specimens mentioned plants in site. Results: There were 40 medicinal plants from 30 families for the treatment of Diabetes Mellitus. The family with most plant was Fabaceae 5 (16.67 %). Herbal medicines are often used in the form of decoction (45%) and dried powder (33%). It was found that Momordica charantia Linn. (42.5%) and Syzygium jambos Lam. (40%) were two most frequently used plants among traditional healers for the treatment of Diabetes. Conclusions: Based on the current findings many of the mentioned plants could have potential active ingredients to influence Diabetes Mellitus and could provide preliminary data for further phytochemical investigations which could possibly lead in the development of novel drugs with little or no side effects and transferring it to future generation. Furthermore, such practical ethno botanical knowledge which is generated based on their intimate experience accumulated over many generations could be helpful in rescuing disappearing knowledge and invention of new drugs of many diseases.